2002
DOI: 10.1038/sj.onc.1205175
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic potential of the DNA replication licensing protein CDT1

Abstract: The expression of a gene, designated as Retroviral insertion site (Ris)2, was activated by retroviral DNA integration in an immortalized primitive erythroid cell line, EB-PE. Ris2 was also expressed at high levels in all human tumor cell lines analysed. Consistently, NIH3T3 ®broblasts overexpressing Ris2 formed tumors in Rag2 7/7 mice when injected subcutaneously. The putative RIS2 protein shows a high sequence similarity to Xenopus CDT1, Drosophila DUP, and human CDT1, a newly identi®ed DNA replication licens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 48 publications
9
108
0
7
Order By: Relevance
“…In higher eukaryotes, many pathways converge upon Cdt1 to prevent re-replication, including degradation in S-phase by two distinct pathways and inhibition by geminin. Cdt1 levels are often elevated in tumors (23), and overexpression of Cdt1 in mice can lead to tumors (24). This guilt by association and causality suggests that high levels of Cdt1 may be one pathway to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In higher eukaryotes, many pathways converge upon Cdt1 to prevent re-replication, including degradation in S-phase by two distinct pathways and inhibition by geminin. Cdt1 levels are often elevated in tumors (23), and overexpression of Cdt1 in mice can lead to tumors (24). This guilt by association and causality suggests that high levels of Cdt1 may be one pathway to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high levels of Cdt1 appear to have a causative role in cancer. It has been shown that retrovirally activated Cdt1 can be oncogenic in mice (24) and that Cdt1 overexpression in thymocytes can cause lymphomas when p53 is also mutated. As Cdt1 overexpression causes re-replication in a variety of systems, it is possible that high levels of Cdt1 induce genomic instability and tumorigenesis by inducing re-replication.…”
mentioning
confidence: 99%
“…However, deregulation of the licensing system may also be a primary driver of oncogenesis, at least in some tumour types. For example, over-expression of Cdc6 or Cdt1 have been shown to be oncogenic, and deregulated Mcm7 expression has been linked to tumour formation, progression and malignant transformation in animal models [84][85][86][87][88][89][90]. Oncogenic mutations in genes upstream of the licensing machinery (eg RAS, CYCLINE and CYCLIND1 ) can also impact on tumourigenesis by causing deregulation of the licensing machinery.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%
“…The deletion was localized in a Cdt1 region, which is rich in acidic, serine, threonine and proline residues, and corresponds to a previously uncharacterized PEST-like domain (hereafter referred as to 'PEST') that we also detected in other Cdt1 homologues ( Supplementary Fig. S1) 10,24,25 . As the mutation induced an in-frame deletion The homozygous mutation of Cdt1 consists in an 18-nucleotide deletion leading to a six-amino acid in-frame deletion within the PEST domain (D 6 PEST).…”
Section: Resultsmentioning
confidence: 96%
“…Inappropriate licensing (for instance, as a consequence of deregulated Cdt1 activity) leads to origin reactivation, re-replication, genomic stress and instability and, ultimately, to oncogenic transformation 5,[8][9][10] . Cdt1 activity is controlled by several, partly redundant pathways.…”
mentioning
confidence: 99%